2015
DOI: 10.1016/j.ejrnm.2015.03.006
|View full text |Cite
|
Sign up to set email alerts
|

The role of diffusion-weighted magnetic resonance imaging in T staging and grading of urinary bladder cancer

Abstract: Purpose: To evaluate the ability of diffusion-weighted imaging (DWI) in T staging of urinary bladder cancer and the correlation between the apparent diffusion coefficient (ADC) and tumor grading. Patients and methods: This study included 40 patients with bladder mass diagnosed by ultrasonography. MR imaging sequences included, T2WI, DWI, ADC and T1 postcontrast MRI were done. The correlation between magnetic resonance findings and histopathological results was done. Results: Of all forty patients, 14 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…In the current study, all bladder tumors were clearly visible in DWI at a high b value (1000 s/mm 2 ) as a bright SI relative to the bladder wall and surrounding tissue with 98% sensitivity as previously reported by other researchers [ 12 , 20 , 21 ]. Also, and in accordance with others [ 22 , 23 ], there was a statistically significant difference between malignant and benign bladder wall pathologies.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In the current study, all bladder tumors were clearly visible in DWI at a high b value (1000 s/mm 2 ) as a bright SI relative to the bladder wall and surrounding tissue with 98% sensitivity as previously reported by other researchers [ 12 , 20 , 21 ]. Also, and in accordance with others [ 22 , 23 ], there was a statistically significant difference between malignant and benign bladder wall pathologies.…”
Section: Discussionsupporting
confidence: 88%
“…Regarding differentiation of organ confined from non-organ confined BC, staging accuracy of DWI alone was 77.4% which was higher than El-Assmy's et al (69.6%) [ 30 ] and lower than Abdel-Rahman et al [ 20 ] and Wu et al [ 29 ] who reported accuracy between 90–95%. DWI plus T2WI had a higher accuracy (83%) in differentiating organ confined from non-organ confined tumors as compared to T2WI alone (75.9%) or DWI alone (77.4%).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…DWI was reported to have an accuracy of 63.6%, 75.7%, 93.7%, and 87.5% for diagnosing tumour stages T1, T2, T3, and T4, respectively. According to Abdel-Rahman et al [16], DWI's accuracy in tumour staging ranged from 85.7% to 77.8% to 50% across stages T1 and T3. In comparison to El-Assmy et al [13] and Abdel-Rahman et al [16], the present study's findings indicated considerably better accuracy for T1 and T2 staging, at 90% and 85.7% respectively, and accuracy for T3 staging, at 66.7%.…”
Section: Discussionmentioning
confidence: 99%